2022
DOI: 10.1111/rda.14086
|View full text |Cite
|
Sign up to set email alerts
|

Association among metabolic status, oxidative stress, milk yield, body condition score and reproductive cyclicity in dairy buffaloes

Abstract: The aim of this study was to determine the metabolic status, stress and ovarian activity through progesterone profile in dairy buffalo as influenced by post‐partum days, body condition score (BCS) and lactation number. A total of 45 dairy buffaloes were involved and divided into three factors based on their BCS (2.5, 3.0 and 3.5, respectively), lactation number (1, 2 and 3, respectively), and post‐partum intervals (14, 28, 42 and 56, respectively). Based on findings, from day 14 to day 56 after parturition, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Among them, P4 is converted from free cholesterol through diverse rate-limiting enzymes, including steroid-derived acute regulatory enzyme (StAR), 3-β-hydroxysteroid dehydrogenase, and P450 side chain lyase [ 4 ]. Furthermore, in female animals, P4 is involved in the regulation of physiological processes such as menstrual cycle, pregnancy, and lactation [ 5 , 6 , 7 ]. In view of the central role of GC in the ovary, it is of great significance to clarify the mechanism of P4 synthesis in GCs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, P4 is converted from free cholesterol through diverse rate-limiting enzymes, including steroid-derived acute regulatory enzyme (StAR), 3-β-hydroxysteroid dehydrogenase, and P450 side chain lyase [ 4 ]. Furthermore, in female animals, P4 is involved in the regulation of physiological processes such as menstrual cycle, pregnancy, and lactation [ 5 , 6 , 7 ]. In view of the central role of GC in the ovary, it is of great significance to clarify the mechanism of P4 synthesis in GCs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the study found a significant increase in overall milk yield among dairy cows with high serum calcium levels (Ca-H) compared to those with medium (Ca-M) and low (Ca-L) levels. The heightened demand for calcium during lactation in dairy animals, coupled with the observed physiological decrease in plasma calcium after parturition, likely contributes to orchestrated hormonal adaptations supporting calcium balance and, consequently, increased milk production (Saqib et al, 2022). Abbreviations: Ca-L, calcium low (<5 mg/dL); Ca-M, calcium medium (5-8.5 mg/dL); Ca-H, calcium high (>8.5 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the SFAM may have preserved body fat reserves indicative of the BCS by improving net energy balance in early lactation [ 5 , 21 ]. These findings indicate that NSF cows were more nervous and, as a result, had lower MYM and milk quality than OSF cows because increased metabolic stress during machine milking negatively affects energy metabolism and metabolic stress indicators, such as cortisol and malondialdehyde [ 42 , 43 ]. This case indicates that buffalo cows can have individual personality traits that affect their behaviours and thus regulate how they meet these needs in addition to their metabolic and physiological needs regarding precision feeding, as in dairy cattle [ 21 , 43 ].…”
Section: Discussionmentioning
confidence: 99%